Vitamin D Is Required for ILC3 Derived IL-22 and Protection From Citrobacter rodentium Infection - Lin, Yang-Ding; Arora, Juhi; Diehl, Kevin; Bora, Stephanie A.; Cantorna, Margherita T. (Frontiers in Immunology, 2019)
Citrobacter rodentium is a gastrointestinal infection that requires early IL-22 from group 3 innate lymphoid cells (ILC3) for resistance. The role of vitamin D in the clearance of C. rodentium infection was tested in vitamin D sufficient (D+) and vitamin D deficient (D-) wildtype (WT) and Cyp27B1 (Cyp) KO mice (unable to produce the high affinity vitamin D ligand 1,25(OH)2D, 1,25D). Feeding Cyp KO mice D- diets reduced vitamin D levels and prevented synthesis of 1,25D. D- (WT and Cyp KO) mice had fewer ILC3 cells and less IL-22 than D+ mice. D- Cyp KO mice developed a severe infection that resulted in the lethality of the mice by d14 post-infection. T and B cell deficient D- Rag KO mice also developed a severe and lethal infection with C. rodentium compared to D+ Rag KO mice. D- WT mice survived the infection but took significantly longer to clear the C. rodentium infection than D+ WT or D+ Cyp KO mice. Treating infected D- Cyp KO mice with IL-22 protected the mice from lethality. Treating the D- WT mice with 1,25D reconstituted the ILC3 cells in the colon and protected the mice from C. rodentium. IL-22 treatment of D- WT mice eliminated the need for vitamin D to clear the C. rodentium infection. Vitamin D is required for early IL-22 production from ILC3 cells and protection from enteric infection with C. rodentium.